Social Computing, Behavioral - Cultural Modeling and Prediction 5th International Conference, SBP 2012, College Park, MD, USA, April 3-5, 2012. Proceedings - Yang, Shanchieh Jay.; Greenberg, Ariel M.; Endsley, Mica.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 5th International Conference on Social Computing, Behavioral-Cultural Modeling and Prediction, held in College Park, MD, USA, in April 2012. The 43 revised papers presented in this volume were carefully reviewed and selected from 76 submissions. The papers cover a wide range of topics including economics, public health, and terrorist activities, as well as utilize a broad variety of methodologies, e.g., machine learning, cultural modeling and cognitive modeling.
Keywords: Computer science; Computer communication systems; Data mining; Application software; Computers and civilization; Management information systems; Computer Science; Computers and Society; Computer Appl. in Social and Behavioral Sciences; Management of Computing and Information Systems; Data Mining and Knowledge Discovery; Computer Communication Networks; Information Systems Applications (incl. Internet).; Electronic books